Analysis of Internal and External Factors Influence on Leading Development of Incentive Travel Product in Pulau Harapan Kepulauan Seribu Jakarta - Yosi Erfinda; Rinie Octaviany Hasan; Revi Agustin Aisyianita; Rezka Fedrina; Raihana Hafidzah Jumartin; Sabrina Azzahra; Nabil Falah (Journal of Tourism and Economic, 2025)
Incentive travel is a key segment in MICE that aims to motivate employees. Although Indonesia is a leading MICE destination, the competitiveness of Jakarta has not been optimized as an incentive travel destination. This study identifies Harapan Island in the Thousand Islands as Jakarta's leading potential for incentive travel, offering unique maritime and conservation experiences. However, there is a significant gap between this potential and the current unstructured and uncompetitive tourism products, which fail to meet corporate expectations. Using quantitative associative methods, this study analyzes the influence of internal factors (accommodation, cuisine) and external factors (accessibility, local support) on destination competitiveness. Data from 50 respondents, mostly tourism workers and corporate employees, was collected through a reliable questionnaire (Cronbach's Alpha >0.90) and found to have a normal distribution. The findings confirm the strong potential of Harapan Island, but highlight critical weaknesses in supporting facilities and product packaging. This study concludes that community-based strategic development for premium products is essential to transform Harapan Island into a competitive and sustainable incentive travel destination, thereby supporting the vision of “Jakarta Nice for MICE.”